Incidence of secondary glaucoma after treatment of uveal melanoma with robotic radiosurgery versus brachytherapy. Issue 8 (7th April 2017) - Siedlecki, Jakob; Reiterer, Veronika; Leicht, Simon; Foerster, Paul; Kortüm, Karsten; Schaller, Ulrich; Priglinger, Siegfried; Fuerweger, Christoph; Muacevic, Alexander; Eibl‐Lindner, Kirsten
ABSTRACT: Purpose: Different modalities of radiation therapy nowadays allow for effective treatment of uveal melanoma combined with the advantage of eye preservation. However, this advantage can secondarily be impaired by radiation‐related side effects. After local recurrence, secondary glaucoma (SG) has been described as second most frequent complication leading to need of enucleation. This study compares the incidence of SG after conventional Ruthenium (Ru)‐106 brachytherapy (BT) versus CyberKnife robotic radiosurgery (RRS) which has been gaining importance lately as an efficient treatment option offering improved patient comfort. Methods: Medical records of all patients diagnosed with uveal melanoma in the Eye Clinic of the Ludwig‐Maximilians‐University Munich between 2007 and 2013 were reviewed. A total of 268 eyes of 268 patients treated with Ru‐106 BT or CyberKnife‐RRS as monotherapy were entered in this retrospective cohort study. Incidence of SG was correlated with treatment modality and baseline tumour characteristics. Results: Fifty‐three patients (19.8%) developed SG. At 5 years, SG was significantly more frequent after RRS (46.7%) than BT (11.1%); however, tumour thickness (maximum apical height) as a marker of tumour progress was more pronounced in the RRS group. Subgroup analysis of 178 patients for tumours amenable to both BT and RRS (thickness ≤6 mm) revealed comparable results at 3 years (RRS: 13.8 versus BT: 11.2%), but a trend towards increased incidence after RRS beyond year three. However, this difference was not significant at 5 years (28.2% versus 11.2%, p = 0.138). Tumour thickness was significantly associated with incidence of SG. Conclusion: In tumours ≤6 mm thickness, RRS and BT seem to offer a comparable safety profile in terms of SG. Beyond year three, SG was tendentially, but not significantly more frequent after RRS. Increasing tumour thickness is associated with risk of SG.